Penguatan Literasi Numerasi melalui Pembelajaran Matematika Inovatif sebagai Strategi Peningkatan Kualitas Pendidikan - Alisda Rasty Amellia Putri; Nabila Cahyaning Putri; Andin Anjelika Tiara Sasabila; Anggi Dwi Lestari; Dyandra Ramadhani (Universitas PGRI Madiun, 2026)
This study aims to describe the strengthening of numeracy literacy through innovative mathematics learning to improve the quality of education in elementary schools. The research employed a qualitative descriptive approach. Data were collected through semi-structured interviews with an elementary school teacher and analyzed using thematic analysis. The findings indicate that the implementation of Problem Based Learning (PBL), Project Based Learning (PjBL), game-based learning, and the use of concrete and digital learning media enhanced students’ participation, critical thinking, self-confidence, and numeracy skills. Despite several challenges, innovative mathematics learning effectively supports numeracy literacy development and contributes to improving the quality of elementary education.